Urdu ka guldasta Champa - Fauzia Ehsan Farooqi (Karachi: Oxford University Press., 2022)
Urdu Ka Guldasta Champa* is an engaging and educational Urdu language textbook designed to enhance students' reading, writing, and comprehension skills. Featuring a rich assortment of prose, poetry, and short stories, the book introduces students to the beauty of Urdu literature, ranging from classical to contemporary works. The lessons are structured to improve vocabulary, grammar, and creative writing abilities, while fostering critical thinking and cultural appreciation. With thoughtfully crafted exercises and activities, this textbook serves as an essential tool for students to build a strong command of the Urdu language and a deeper connection to its literary heritage.